Deep procedural sedation by a sedationist team for outpatient pediatric renal biopsies. (12th February 2016) - Kamat, Pradip P.; Ayestaran, Frank W.; Gillespie, Scott E.; Sanders, Rebecca D.; Greenbaum, Larry A.; Simon, Harold K.; Stockwell, Jana A.
Abstract: To date, no study has analyzed the use of deep PS for pediatric renal biopsies by a dedicated sedation team in an outpatient setting. Retrospective analysis of renal biopsies performed at CHOA from 2009 to 2013. Patient demographics, procedure success, and sedation‐related events were analyzed. Logistic regression techniques were applied to identify characteristics associated with procedure safety and success. A total of 174 biopsies from 136 patients, aged 2–21 yr, were reviewed. Of the 174 biopsies, 63 of 174 (36%) were from native, and 111 of 174 (64%) were from transplanted kidneys, respectively. No deaths, allograft losses, or unanticipated hospital admissions occurred. The most commonly utilized interventions during sedation were blow‐by oxygen (29.9%) and CPAP (12.1%). Children receiving the combination of F + P had significantly higher biopsy success rates vs. other drug combinations (96.1% vs. 79%; p = 0.014). There was no difference in complication rates regardless of drug combination or biopsy type (transplanted vs. native). The combination of F + P yields a high procedural success rate for outpatient native and transplanted kidney biopsies. We identified a number of sedation‐related events that can be easily managed by a well‐trained sedationist team.